(untitled) (Revista Brasileira de Contabilidade e Gestão, 2018)
The objective of the present study is to verify if there are significant differences in the economic- financial indicators of companies that operate in specific segments of the Brazilian Transport Sector. The methodological procedures characterize the research as descriptive and documentary, with quantitative information approach. The sample is formed by nine companies, distributed in the transport segments air, rail, waterway and road. The analysis period comprised the years 2010 to 2016. Data analysis was performed using descriptive statistics, Kruskal-Walls mean difference test, using SPSS® software, version 20.0. The results showed that the economic and financial performance of the companies that make up the transportation segments differ in terms of short-term indicators, such as indebtedness, payment capacity and return on investment. It was also observed that these companies are dependent on long-term third-party capital to finance their fixed asset, which is justified by the high volume of investments required by the segment.